2002
DOI: 10.1074/jbc.m202469200
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NFIC Undergoes N-Glycosylation during Early Mammary Gland Involution

Abstract: Expression of a 74-kDa nuclear factor I (NFI) protein is triggered in early involution in the mouse mammary gland, and its expression correlates with enhanced occupation of a twin (NFI) binding element in the clusterin promoter, a gene whose transcription is induced at this time (Furlong, E. E., Keon, N. K., Thornton, F. D., Rein, T., and Martin, F. (1996) J. Biol. Chem. 271, 29688 -29697). We now identify this 74-kDa NFI as an NFIC isoform based on its interaction in Western analysis with two NFIC-specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 68 publications
1
33
1
Order By: Relevance
“…NFIC also has been reported previously to be modified by N-glycosylation [5]. Kane et al have reported that a 74 kDa N-glycosylated NFIC isoform appears during mammary gland involution [9]. But the specific role of this N-glycosylated isoform is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NFIC also has been reported previously to be modified by N-glycosylation [5]. Kane et al have reported that a 74 kDa N-glycosylated NFIC isoform appears during mammary gland involution [9]. But the specific role of this N-glycosylated isoform is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have shown previously that the NFI-B2 isoform displayed an increased binding affinity as compared to the NFI-X1 and NFI-A4 isoforms to the WAP promoter. Subsequent studies by other investigators have also revealed the differential binding affinity of specific NFI isoforms to their DNA binding motifs in other promoters [9]. While these differences in DNA binding affinity may help facilitate the specific competition of one NFI isoform with other NFI proteins, these differences alone may not be sufficient to account for their selective ability to cooperate with the other transcription factors for the regulation of the mammary-specific genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycosylation is a major form of posttranslational modification and its regulatory roles in the context of different transcription factors such as CREB, NF1C, Oct-2, Sp1 and STAT5 have been documented (Jackson and Tjian, 1988;Kane et al, 2002;LamarreVincent and Hsieh-Wilson, 2003;Gewinner et al, 2004;Ahmad et al, 2006). In addition, ATF6, another membrane-bound bZIP transcription factor activated by RIP in response to ER stress, is also known to be N-linked glycosylated and this modification has an impact on its transcriptional activity (Hong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%